Figurative Language and Imagery in the Lyrics of Diskoria's Songs on the Intonesia Album and Their Relevance as Teaching Material for Learning to Write Poetry in High School: Gaya Bahasa dan Citraan dalam Lirik Lagu Diskoria pada Album Intonesia dan Relevansinya Sebagai Bahan Ajar Pembelajaran Menulis Puisi di SMA - Miftahul Janah; Sendang Mulyono (Universitas Negeri Semarang, 2025)
Song lyrics are a form of popular literary work that contains many elements of stylistics and imagery. This study aims to analyze the figures of speech and imagery in the lyrics of Diskoria's songs on the album Intonesia (2024-2025) and explain their relevance as teaching materials for writing poetry in the eleventh grade of high school. The method used is descriptive qualitative with documentation and content analysis techniques. The results of the analysis showed that there were 152 findings of figures of speech and 88 of imagery. The most frequently appearing figures of speech are metaphor and personification, while the dominant imagery is visual and kinesthetic. The element of figurative language functions to convey feelings, highlight differences in meaning, clarify the relationship between ideas, and create rhythm. Imagery is used to create a more concrete picture and strengthen the meaning of the lyrics. These findings indicate that figures of speech and imagery not only beautify the form, but also help convey the content and emotions of the song more effectively. Based on linguistic, psychological, and cultural background aspects, Diskoria's songs are considered suitable for use as teaching materials because they are in accordance with the abilities, experiences, and emotional closeness of students, as well as being relevant as a source of inspiration in learning to write poetry. This research is expected to expand the application of stylistic analysis in literature learning in schools. Lirik lagu merupakan salah satu bentuk karya sastra populer yang mengandung banyak unsur stilistika dan citraan. Penelitian ini bertujuan untuk menganalisis gaya bahasa dan citraan dalam lirik lagu Diskoria pada album Intonesia (2024-2025) serta menjelaskan relevansinya sebagai bahan ajar menulis puisi di kelas XI SMA. Metode yang digunakan adalah kualitatif deskriptif dengan teknik dokumentasi dan analisis isi. Hasil analisis menunjukkan bahwa terdapat 152 data temuan gaya bahasa dan 88 citraan. Gaya bahasa yang paling sering muncul adalah metafora dan personifikasi, sementara citraan yang dominan adalah visual dan kinestetik. Unsur gaya bahasa berfungsi untuk menyampaikan perasaan, menonjolkan perbedaan makna, memperjelas hubungan antar gagasan, serta menciptakan irama. Citraan digunakan untuk menciptakan gambaran yang lebih konkret dan memperkuat makna lirik. Temuan ini menunjukkan bahwa gaya bahasa dan citraan tidak hanya memperindah bentuk, tetapi juga tetapi juga membantu menyampaikan isi dan emosi lagu secara lebih efektif. Berdasarkan aspek bahasa, psikologi, dan latar budaya, lagu-lagu Diskoria dinilai layak digunakan sebagai bahan ajar karena sesuai dengan kemampuan, pengalaman, dan kedekatan emosional peserta didik, sekaligus relevan untuk dijadikan sumber inspirasi dalam pembelajaran menulis puisi. Penelitian ini diharapkan dapat memperluas penerapan analisis stilistika dalam pembelajaran sastra di sekolah.